Acceptance of national and store brands of wine by supermarket consumers in the South of Chile - Schnettler,Berta (2012)
The relative importance of brand (traditional national, new or emerging national and store brand), packaging (bottle and tetra-pack) and price on the choice of red wine were evaluated through consumers in Temuco, and consumer segments were also identified in terms of their preferences. 400 direct surveys were applied in September 2010. Of all those surveyed, 79.8% said they drank wine, predominantly occasionally. Brand (60.4%) was more important than price (21.8%) and packaging (17.8%). Three segments were identified: the largest (81.5%) said brand was most important; the second (11%) attributed similar relevance to packaging and price; the third (7.5%) said price was the most important. The groups differed according to socio-demographic characteristics, influences on the decision to purchase and the motives for choosing the brand. Independently of the importance given to brand, consumers preferred the widely known national brands at the lowest price, and rejected the store-brand wine.